Species Diversity of Soil Insect in the Lemor Botanical Garden, East Lombok, Indonesia - Sari, Yuli Novita; Artayasa, I Putu; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Soil insects play an important role as environmental indicator organisms, ecosystem balancers, and decomposers of organic matter. This study aims to determine the diversity of soil insects in the Lemor Botanical Garden, East Lombok. The diversity of flora and fauna in this area makes it suitable as a conservation site that also serves educational purposes. Sampling was conducted using pitfall traps, soil borers, and Berlese-Tullgren funnels at two stations: station 1 (ex situ) and station 2 (in situ). Data were analyzed using the Shannon-Wiener diversity index. The results showed that 44 species of soil insects were found, belonging to 11 orders and 23 families, with a total of 970 individuals. The most dominant species belonged to the family Formicidae, with 257 individuals. Overall, the soil insect diversity index on litter was H' = 1.778, on the soil surface H' = 2.265, and in the soil layer H' = 1.098. These results indicate that the diversity level of soil insects in the Lemor Botanical Garden is moderate and varies across habitat layers. This moderate diversity reflects a relatively stable ecosystem and supports the importance of Lemor Botanical Garden as a site for conservation and environmental education.